Convergence of diffusion processes - Makhno , S. Ya. (Ukrains’kyi Matematychnyi Zhurnal, 1992)
For stochastic diffusion equations with coefficients depending on a parameter, necessary and sufficient conditions of the weak convergence of solutions to the solution of a stochastic diffusion equation are obtained.